FreshLanDiv: A global database of freshwater biodiversity across different land uses - Shen, Minghua; Klink, Roel van; Sagouis, Alban; K. Petsch, Danielle; Abong'o, Deborah Atieno; Alahuhta, Janne; Abdo Al-Shami, Salman; Armendáriz, Laura Cecilia; Bae, Mi-Jung; Abdul, Nurul Huda (John Wiley & Sons, 2024)
Motivation: Freshwater ecosystems have been heavily impacted by land-use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land-use categories. This compilation will be useful for addressing questions regarding land-use change and its impact on freshwater biodiversity. Main Types of Variables Contained: The database includes metadata of each study, sites location, sample methods, sample time, land-use category and abundance of each taxon. Spatial Location and Grain: The database contains data from across the globe, with 85% of the sites having well-defined geographical coordinates. Major Taxa and Level of Measurement: The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.